Pengaruh Pendapatan dan Tingkat Pendidikan terhadap Konsumsi Rumah Tangga Provinsi Jambi Periode 2019-2023 - Nur Ismi Nabila; Agustina Mutia; Sri Rahma (Lembaga Yasin AlSys, 2025)
Although household consumption has long been a central focus in economic studies, research that specifically examines the influence of income and education level on household consumption in Jambi Province using recent panel data remains relatively limited. This study aimed to analyze the effect of income and education level on household consumption in Jambi Province during the 2019–2023 period, both partially and simultaneously. A quantitative approach with a panel data design was employed, using secondary data from the Jambi Province Central Bureau of Statistics (Badan Pusat Statistik/BPS) and BPS of regencies/cities in Jambi Province for the 2019–2023 period. The data were analyzed using descriptive statistics and panel data regression, including model selection through the Chow test, Hausman test, and Lagrange Multiplier test, as well as hypothesis testing using the t-test and F-test with the assistance of EViews 12 software. The findings indicated that, partially, income had a positive and significant effect on household consumption in Jambi Province, and education level likewise had a positive and significant effect on household consumption. Simultaneously, income and education level had a significant effect on household consumption in Jambi Province during the 2019–2023 period. These results affirm that income and education level are important factors in promoting higher household consumption and should be prioritized in the formulation of policies aimed at improving societal welfare. The implications of this study provide input for local governments in designing policies oriented toward strengthening income and expanding access to education to enhance household welfare.